Plant-derived human butyrylcholinesterase, but not an organophosphorous-compound hydrolyzing variant thereof, protects rodents against nerve agents - Geyer, Brian C.; Kannan, Latha; Garnaud, Pierre-Emmanuel; Broomfield, Clarence A.; Cadieux, C. Linn; Cherni, Irene; Hodgins, Sean M.; Kasten, Shane A.; Kelley, Karli; Kilbourne, Jacquelyn; Oliver, Zeke P.; Otto, Tamara C.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2010)
The concept of using cholinesterase bioscavengers for prophylaxis against organophosphorous nerve agents and pesticides has progressed from the bench to clinical trial. However, the supply of the native human proteins is either limited (e.g., plasma-derived butyrylcholinesterase and erythrocytic acetylcholinesterase) or nonexisting (synaptic acetylcholinesterase). Here we identify a unique form of recombinant human butyrylcholinesterase that mimics the native enzyme assembly into tetramers; this form provides extended effective pharmacokinetics that is significantly enhanced by polyethylene glycol conjugation. We further demonstrate that this enzyme (but not a G117H/E197Q organophosphorus acid anhydride hydrolase catalytic variant) can prevent morbidity and mortality associated with organophosphorous nerve agent and pesticide exposure of animal subjects of two model species.